Stephen Bullivant, Catholicism in the time of Coronavirus, Park Ridge, IL: Word on Fire Catholic Ministries 2020 - Nabożny, Marcin Krzysztof (Studia Nauk Teologicznych PAN, 2021)
The book is divided into 4 chapters followed by an afterword, appendix and notes; the foreword is written by Bishop Robert Barron; sources gotten from books, the internet, and the Catholic Church. Notably, the whole process, from pitch to perfect, happened over the space of twelve days: Monday, March 30 to Friday, April 10, 2020. The book contains a collection of “structured thoughts” about the COVID-19 crisis and its aftermath, and their likely impacts upon the Church’s pastoral and evangelistic mission, focusing on the Catholic Church in the US and UK. Chapter 2 has a table on annual average percentage change in typical Sunday mass attendance in England and Wales, and 22 US (arch)dioceses.